2015
DOI: 10.1097/ta.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa wound infection involves activation of its iron acquisition system in response to fascial contact

Abstract: Background Wound infections are traditionally thought to occur when microbial burden exceeds the innate clearance capacity of host immune system. Here we introduce the idea that the wound environment itself plays a significant contributory role to wound infection. Methods We developed a clinically relevant murine model of soft tissue infection to explore the role of activation of microbial virulence in response to tissue factors as a mechanism by which pathogenic bacteria cause wound infections. Mice underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…We provide evidence that the pathogenesis of A. baumannii wound infections is dependent on the degree of tissue trauma and the composition of the wound milieu. We have previously shown that the wound environment plays a significant contributory role in infectious pathogenesis using a Pseudomonas aeruginosa wound infection model in which rectus muscle injury providing contact with fascia was sufficient for P. aeruginosa to cause wound infection through activation of its iron scavenging systems (28). However, as our current work demonstrated, a more severe insult combining muscle injury with ischemia was required for A. baumannii wound infection in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We provide evidence that the pathogenesis of A. baumannii wound infections is dependent on the degree of tissue trauma and the composition of the wound milieu. We have previously shown that the wound environment plays a significant contributory role in infectious pathogenesis using a Pseudomonas aeruginosa wound infection model in which rectus muscle injury providing contact with fascia was sufficient for P. aeruginosa to cause wound infection through activation of its iron scavenging systems (28). However, as our current work demonstrated, a more severe insult combining muscle injury with ischemia was required for A. baumannii wound infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, as our current work demonstrated, a more severe insult combining muscle injury with ischemia was required for A. baumannii wound infection in mice. This difference may reflect a higher capacity of P. aeruginosa to trigger its virulence in response to multiple host derived signals (2834), and hence explain, in part, its reputation as a highly virulent pathogen. Without the local microenvironmental cues present in a wound complicated by injury and ischemia, A. baumannii may not be sufficiently activated to cause a clinical wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Their adaptation capacity to grow in diverse ecological niches, their alteration of virulence factor expression and, thus, their pathogenic behaviour due to their interaction with host elements explain their capability to produce a diversity of opportunistic infections [31]. Many strains of this complex are described as host invaders, especially during impairment of immune defence, and they are adequately described as human pathogens in various serious infections including wounds [31,32]. S. lugdunensis, a coagulase-negative coccus, was also isolated from the tissue swabs.…”
Section: Medical Importance Of the Bacteria Isolatedmentioning
confidence: 99%
“…Yet how and why bacteria in some circumstances seem to “be cleared away” is largely unstudied and therefore remains unknown. Advances in molecular microbiology might explain such a response as the net result of a complex and iterative dialogue between pathogen and host whose final interplay ends in a type of “molecular détente (38). ”…”
Section: The Pathogenesis Of Ssis Is Likely To Be More Complex Than Imentioning
confidence: 99%